Ultrahigh strain hardening in a transformation-induced plasticity and twinning-induced plasticity titanium alloy. (October 2020) - Fu, Yu; Xiao, Wenlong; Kent, Damon; Dargusch, Matthew S.; Wang, Junshuai; Zhao, Xinqing; Ma, Chaoli
Abstract: In this study, a design strategy employing stress-induced β to hexagonal α′ martensitic transformation to develop a novel Ti-15Nb-5Zr-4Sn-1Fe alloy with ultrahigh strain hardening rate (~6.1 GPa) is reported. Microstructural investigations reveal that the superior strain hardening response is contributed by stress-induced β to α′ transformation with accompanying reversion of athermal ω and profuse internal { 1 ¯ 011}<10 1 ¯ 2> and {11 2 ¯ 2}<11 2 ¯ 3> α′ mechanical twinning which promote twin-twin interactions, imparting high strength and outstanding uniform elongation. This study may serve as a template for developing new class of transformation-induced plasticity (TRIP) and twinning-induced plasticity (TWIP) Ti alloys based on β to α′ martensitic transformation. Graphical abstract: Image, graphical abstract